Testate amoebae colonizing a newly exposed land surface are of airborne origin. (January 2015) - Wanner, Manfred; Elmer, Michael; Sommer, Michael; Funk, Roger; Puppe, Daniel
Abstract: We hypothesized that at the very beginning of terrestrial ecosystem development, airborne testate amoebae play a pivotal role in facilitating organismic colonization and related soil processes. We, therefore, analyzed size and quantity of airborne testate amoebae and immigration and colonization success of airborne testate amoebae on a new land surface (experimental site "Chicken Creek", artificial post-mining water catchment). Within an altogether 91-day exposure of 70 adhesive traps, 12 species of testate amoebae were identified to be of airborne origin. Phryganella acropodia (51% of all individuals found, diameter about 35–45 μm) and Centropyxis sphagnicola (23% of all individuals found, longest axis about 55–68 μm), occurred most frequently in the adhesive traps. We extrapolated an aerial amoeba deposition of 61 individuals d −1 m −2 (living and dead individuals combined). Although it would be necessary to have a longer sequence (some additional years), our analysis of the "target substrate" of aerial immigration (catchment site) may point to a shift from a stochastic (variable) beginning of community assembly to a more deterministic (stable) course. This shift was assigned to an age of seven years of initial soil development. Although experienced specialists are necessary to conduct these time-consuming studies, the presented data suggest that terrestrial amoebae are suitable indicators for initial ecosystem development and utilization.